AUTONOMOUS VEHICLE - AZIZAN, AZUAN (Universiti Teknologi Petronas, 2005)
The objective of this report is to obtain the current progress of this project, Autonomous Vehicle. This report will discuss about the current status of the project and the theory used to complete this project. This study is done with the aim to interface to the remote controller of a remote control (RC) car and to write a program on the PC that allows the car to travel through pre determined course autonomously. The "intelligence" part of the system can be implemented by using a simple "memory map" or various other techniques e.g. sensor, fuzzy logic, neural network etc. There are two types of sensors used; Infrared (IR) distance sensor and ultrasonic obstacle detector. This project used two ways communication; from PC to RC car, and from sensors to PC. This project has to interface remote controller to computer parallel port. It also has to write a program to activate the parallel port sensors. In simple words the object of this project is to move RC car by using computer. Systematic engineering approach has been applied such as problem definition, literature review, experiment and analysis and communication in order to confine the scope of study as well as to achieve the project objectives. At the end of this report, conclusion and recommendation will be made to summarize up the overall project progress.